2009
DOI: 10.1021/ic901442e
|View full text |Cite
|
Sign up to set email alerts
|

Structural Motifs and Biological Studies of New Antimony(III) Iodide Complexes with Thiones

Abstract: Eight new antimony(III) iodide complexes of the heterocyclic thioamides, 2-mercapto-1-methylimidazole (MMI), 2-mercaptobenzimidazole (MBZIM), 5-ethoxy-2-mercaptobenzimidazole (EtMBZIM), 2-mercaptothiazolidine (MTZD), 3-methyl-2-mercaptobenzothiazole (NMeMBZT), 2-mercapto-3,4,5,6-tetrahydropyrimidine (tHPMT), 2-mercaptopyridine (PYT), and 2-mercaptopyrimidine (PMT) of formulas {[SbI(3)(MMI)(2)].MeOH} (1), [SbI(3)(MBZIM)(2)] (2), {[SbI(2)(mu(2)-I)(EtMBZIM)(2)](2).H(2)O} (3), [SbI(3)(MTZD)] (4), [(NMeMBZT)SbI(2)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 48 publications
3
31
0
3
Order By: Relevance
“…The central six-coordinated antimony atom is adopting pseudo octahedral geometry constituted by two terminal Imt, one bridging Imt and three chlorido ligands. Such ionic species have also been observed for some other antimony complexes for example, [Sb(MBZIM) 4 Cl 2 ]Cl•(H 2 O)(CH 3 OH) 6 and [Sb(MBZI-M) 4 Br 2 ]Br•(H 2 O) (MBZIM=benzimidazole-2-thione).…”
Section: Spectroscopic Studiessupporting
confidence: 53%
See 2 more Smart Citations
“…The central six-coordinated antimony atom is adopting pseudo octahedral geometry constituted by two terminal Imt, one bridging Imt and three chlorido ligands. Such ionic species have also been observed for some other antimony complexes for example, [Sb(MBZIM) 4 Cl 2 ]Cl•(H 2 O)(CH 3 OH) 6 and [Sb(MBZI-M) 4 Br 2 ]Br•(H 2 O) (MBZIM=benzimidazole-2-thione).…”
Section: Spectroscopic Studiessupporting
confidence: 53%
“…[17][18][19] Structural studies on antimony(III) complexes of thioamides have shown that antimony(III) is quite variable in the geometries of its sulfur coordination which can vary between square pyramidal, trigonal bipyramidal and octahedral. [4][5][6][7][8][20][21][22][23][24] The structures are usually distorted because the lone pair of electrons on antimony atom affects the ideal geometry as expected from Valence Shell Electron Pair Repulsion Theory. [4][5][6] These studies further demonstrate that thiones can act both as terminal or bridging ligands [4][5][6][7][8][9][21][22][23][24] leading to the formation of polymeric structures, such as [SbBr 3 (µ 2 -Diaz)(Diaz)] n (Diaz = Diazinane-2-thione).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of lipoxygenase activity (A, %) in the presence of these compounds was calculated according to the process described previously [38]. inhibition with other antimony (III) compounds, they display lower lipoxygenase inhibition than the tin compounds in the literature [14,38].…”
Section: Nmr Spectral Studiesmentioning
confidence: 99%
“…melglumineantimoniate (Glucantime) and sodium stibogluconate (Pentostam)) [9]. The potential anticancer activity of antimony compounds is under consideration [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The last studies indicated that antimony(III) compounds are more active against carcinoma than lymphoma [17].…”
Section: Introductionmentioning
confidence: 99%